ANALISIS IMPLIKASI TEORI BELAJAR TERHADAP PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Syahdan Muhammad Fauzi Syahdan; Ali Maulida (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study addresses the persistent weakness in Islamic Religious Education (PAI) curriculum development, which fails to systematically integrate learning theories, thereby creating a gap between educational ideals and actual learning outcomes. The absence of a psychological foundation rooted in an Islamic worldview further renders PAI instruction predominantly normative and lacking meaningful engagement. Prior research has typically examined learning theories in isolation, inadequately linked them to classical Islamic educational thought, and overlooked their contextualization within the Merdeka Curriculum. This study introduces a novel adaptive integration model grounded in the Islamic worldview, systematically connecting modern and classical learning theories to all PAI curriculum components. Employing library research with a qualitative-philosophical approach, this study analyzes six learning theories alongside PAI curriculum documents (Curriculum 2013 and Merdeka Curriculum). Findings reveal that each theory offers distinct implications for curriculum components, and no single theory suffices independently. Systematic integration of theories centered on tawhid enhances PAI learning effectiveness, particularly in balancing cognitive, affective, and psychomotor domains. The study concludes that PAI curriculum development must adopt an adaptive integration model rooted in the Islamic worldview, utilizing learning theories as instruments to cultivate insan kamil the perfect human being devoted to Allah.